Germany : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper analyzes a very large database of corporate financial statements and ownership information published by Bureau van Dyck, to compare the profitability of German-owned firms located in Germany with that of German-owned firms located outside of Germany. The study relies on data for all nonfinancial, nonmining firms in the Orbis universe that are incorporated in a European country, have average annual sales of at least USD 25 million during 2006-2014, and have financial information available for each year during that period. Orbis coverage is generally considered to be good for continental European countries. For Germany, the coverage in our raw data is between 45 and 55 percent of total sales, using data published in Deutsche Bundesbank (2016) as a reference. The pattern in nonmanufacturing nonretail/wholesale sectors broadly follows that of manufacturing. The only difference is that German-owned firms that are not part of a multinational group are less profitable than their multinational peers, at least in the balanced sample.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet